Halal Tourism in Lombok: Harmonization of Religious Values and Socio-Cultural Identity - Atmo Prawiro (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This study examines the potential of halal tourism by investigating the relationship between religion and socio-cultural identity on the Indonesian island of Lombok. This study draws on a survey of the literature, semi-structured interviews that rely on social responses, and an anthropological approach that is strengthened with data and information from reliable sources. The findings reveal that religious teachings, along with local culture, are one of the positive elements influencing the adoption of halal tourism in Lombok. Islamic principles are represented in the form of physical culture, in addition to those adopted by the society and used as a reference in their daily activity. Furthermore, the interaction between these data supports the existence of a symbiotic relationship exhibited in the form of constructive support between religion, culture, and the tourism business on the island of Lombok within the context of halal tourism.========================================================================================================ABSTRAK – Pariwisata Halal di Lombok: Harmonisasi Nilai Keagamaan dengan Identitas Sosial-Budaya. Peneltian ini mengkaji otentisitas pariwisata halal melalui studi keterkaitan antara agama dan identitas sosial-budaya di Pulau Lombok Indonesia. Metodologi penelitian ini mengunakan kajian pustaka dan wawancara semi struktur untuk mengumpulkan data teoritis berdasarkan respon sosial dan litearatur pariwisata, serta pendekatan antropologis yang diperkaya dengan data dan informasi dari sumber yang kredibel. Penelitian ini menunjukan bahwa ajaran agama melalui proses yang lama beriringan dengan budaya lokal menjadi salah satu faktor positif penerimaan pariwisata halal di Lombok. Nilai-nilai Islam tidak saja tercermin dari tata-nilai yang dianut masyarakat dan menjadi acuan dalam pola tingkah laku mereka, tetapi juga telah termanifestasikan dalam wujud kebudayaan fisik. Lebih jauh temuan penelitian ini mengukuhkan adanya hubungan simbiosis yang diwujudkan dalam bentuk dukungan konstruktif antara agama, adat dan industri pariwisata dalam bingkai pariwisata halal di Pulau Lombok.